Kebijakan Pendidikan di Indonesia : Studi Tentang Upaya Pelaksanaan Kurikulum Merdeka di Sekolah Dasar Oleh Pemerintah Kota Tanjung pinang - Putri Nabila; Yudhanto Satyagraha Adiputra (Perspektif Administrasi Publik dan hukum, 2025)
This study analyzes Indonesian Education Policy through the Implementation of the Merdeka Curriculum in Tanjungpinang City Elementary Schools based on Edward III's policy implementation theory (communication, resources, attitudes/dispositions, bureaucratic structure). This qualitative research evaluates the implementation of the Merdeka Curriculum in Tanjungpinang City Elementary Schools using observation methods and interviews with the Head of the Elementary Development Division. Analysis of communication, resources, disposition, and bureaucratic structure shows effective policy communication through coordination meetings and socialization. The results showed that the communication of the Education Office went well through coordination meetings and socialization, although internal consistency needs to be improved. There is technical guidance for teachers and curriculum derivatives according to Permendikbudristek Number 12 of 2024, but obstacles to teacher adaptation, teaching materials, and infrastructure are found. Teachers' attitudes are positive, influenced by their understanding, resources and work environment. A clear bureaucratic structure supports implementation. In conclusion, implementation shows positive progress, but needs to improve internal communication, resources and continuous evaluation.